APRENDER E ENSINAR GEOGRAFIA MEDIADA POR UMA JORNADA GEOGRÁFICA LITORÂNEA - Alexandre Vítor de Lima Fonsêca; Karen Sheron Bezerra Fonsêca; Kenneth Sebastian Bezerra Fonsêca (Universidade Federal do Maranhão, 2016)
This article reflect on the practice of teaching and the use of a track called Geographical Coastal Day, as a pedagogical resource to teaching and learning Geography. The main objective is to restore the importance of walking on the beaches, streams, wetlands, roads, streets, lanes, alleys and avenues of coastal towns, understanding the landscapes and discussing with the students the itinerary routes in their day to day as, for example, the route home from to school, and school to home: home to creek and creek to home; or house to the beach and beach to home, among other routes, with predetermined and previously mapped paths. In order to achieve this, the environment study was the methodology in which we discuss the tracks as a teaching resource in the light of their importance for the study of geographical space from the living space, and the understanding of environmental reality outside the classroom, which excites the curiosity to ask the reasons of the studied facts, besides stimulating the relationship between theory and practice in a permanent dialectical process, emphasizing the landscape elements as instruments and exploring the data obtained in the field through the graphical, photographic, cartographic and textual languages. With the achieved results, it is intended to systematize those languages and use them in the classroom during the school year, in order to enhance the cultural identity of the student associated with the place, through the perception of landscape elements, identified in the continent/ocean interface.